Impact of prechlorination on organophosphorus pesticides during drinking water treatment: Removal and transformation to toxic oxon byproducts. (15th November 2016) - Li, Wei; Wu, Ruiqing; Duan, Jinming; Saint, Christopher P.; van Leeuwen, John
Abstract: Prechlorination is commonly used to minimize operational problems associated with biological growth as well as taste and odor control during drinking water treatment. However, prechlorination can also oxidise micropollutants into intermediate byproducts. This could impose profound effects on the safety of the finished water if the transformed byproducts are more toxic and less removable. This study investigated the effect of prechlorination on decomposition and subsequent removal of the four organophosphorus pesticides (OPPs): chlorpyrifos, diazinon, malathion and tolclofos-methyl using a simulated conventional water treatment process of powdered activated carbon assisted coagulation-sedimentation-filtration (PAC-CSF) and postchlorination. It was found that, following prechlorination, not only did the percentage of OPPs oxidation vary significantly, but also the concentration of transformed oxons, which are more toxic than their parent compounds, increased as the major identified oxidation byproducts in water. Removal of these oxons proved to be more difficult by the PAC-CSF than their parent OPPs, because they are more water soluble and more hydrophilic. Both the OPP oxidation and oxon formation increased with chlorine dose during prechlorination. Meanwhile, the continuing chlorination of OPPs by residual free chlorine during PAC-CSF further complicated the pesticide removal processes, generally resulting in a gradually increased formation of oxons. Moreover, in the final treatment stage of postchlorination, the more chlorine-reactive pesticides, malathion and diazinon, were completely oxidised and the formation of corresponding oxons was increased with the prechlorine dose. In contrast, a certain amount of the less chlorine-reactive pesticide tolclofos-methyl still remained in solution after postchlorination, accompanied by an increased formation of tolclofos-methyl oxon with prechlorine dose. Since the oxons are resistant to further oxidation and less adsorbable during the PAC-CSF process, the gross removal of these pesticides and their oxons decreased with increase of the prechlorine dose. This led to an accumulation of the more toxic oxons in the finished water, especially at higher chlorine doses during prechlorination. The significance of this work is the demonstration that, under circumstances where prechlorination is used and source water contains traces of OPPs, alternative practices should be prioritized to avoid the potential risks involved in consumption of the treated water. Graphical abstract: Highlights: Amount of toxic oxons in finished water increased with prechlorine dose. Gross removal of OPPs and their toxic oxons decreased with prechlorine dose. The more chlorine-reactive and less absorbable OPPs have smaller gross removal. Molar ratio of OPPs to oxons varies with OPP species, but not with chlorine dose.